2018
DOI: 10.1002/adbi.201800102
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation in Endotoxin‐Free Albumin Generates Pristine Graphene with Reduced Inflammatory Properties

Abstract: mechanical strength. Within the GBMs, pristine graphene (pG) presents key advantages; its virtually defect-free surface enhances its mechanical properties and the absence of oxygen groups increases its electrical and optical conductivity compared to functionalized graphene, [7] presenting opportunities to develop new biomedical devices. Moreover, since no additional chemical modifications are required, the use of pG would have a positive environmental and economic impact over functionalized graphenes, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 59 publications
0
16
1
Order By: Relevance
“…We found that FLG was internalized within the cells through passive diffusion or phagocytosis. As inflammasome activation is induced by a wide range of stimuli, such as microorganisms, metabolic dysregulation as well as by nanomaterials [34], phagocytosed FLG was predicted to evoke inflammasome activity, however, in this study we did not observe any significant increase in inflammasome-dependant IL-1β production. This was accompanied by no significant secretion of other pro-inflammatory cytokines such as IL-6 and TNF-α.…”
Section: Discussioncontrasting
confidence: 80%
“…We found that FLG was internalized within the cells through passive diffusion or phagocytosis. As inflammasome activation is induced by a wide range of stimuli, such as microorganisms, metabolic dysregulation as well as by nanomaterials [34], phagocytosed FLG was predicted to evoke inflammasome activity, however, in this study we did not observe any significant increase in inflammasome-dependant IL-1β production. This was accompanied by no significant secretion of other pro-inflammatory cytokines such as IL-6 and TNF-α.…”
Section: Discussioncontrasting
confidence: 80%
“…Bone-marrow-derived macrophages (BMDMs) were generated as described previously by our group ( Lebre et al, 2018 ). Briefly, bone marrow cells were extracted from the leg bones and were cultured in high glucose DMEM, supplemented with 8% v/v fetal bovine serum (FBS), 2 mM L-glutamine, 50 U ml –1 penicillin, 50 μg ml –1 streptomycin (hereafter referred to as complete DMEM [cDMEM]).…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow-derived macrophages (BMDMs) were generated as described previously by our group (Lebre, Hanlon, Boland, Coleman, & Lavelle, 2018). Briefly, bone marrow cells were extracted from the leg bones and were cultured in high glucose DMEM, supplemented with 8% v/v fetal bovine serum (FBS), 2 mM L-glutamine, 50 U ml -1 penicillin, 50 μg ml -1 streptomycin (hereafter referred to as complete DMEM [cDMEM]).…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow-derived macrophages (BMDMs) were generated as described previously by our group. (Lebre, Hanlon, Boland, Coleman, & Lavelle, 2018) Briefly, bone marrow cells were extracted from the leg bones and were cultured in high glucose DMEM, supplemented with 8% v/v fetal bovine serum (FBS), 2 mM L-glutamine, 50 U ml -1 penicillin, 50 μg ml -1 streptomycin (hereafter referred to as complete DMEM [cDMEM]). Cells were plated on non-tissue cultured treated petri dishes (Corning) and supplemented with 25% v/v of L929 cell line conditioned medium containing macrophage colonystimulating factor (M-CSF) on day -8.…”
Section: Cell Isolation and Culturementioning
confidence: 99%